Government and Indigenous Community Synergy in Handling Covid-19 Through Local Wisdom Values in North Maluku - Nam Rumkel Rumkel; Hendra - Karianga; Kadaruddin - Kadaruddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
There are 4 sultanates in Moloku Kie Raha (North Maluku). Indigenous Peoples through the Moloku Kie Raha Sultanate institution actively participate in helping meet the needs of the community, as a form of contribution to mitigating the impact of Covid-19. This research aims to find out the role of indigenous peoples in preventing and overcoming Covid-19 through the values of local wisdom in North Maluku, as well as the synergies and patterns of handling carried out by the regional government and the Sultanate in fighting Covid-19 in North Maluku. This research method is socio-juridical, using statutory and conceptual approaches, the data used are primary data and secondary data, and all data collected is analyzed qualitatively. The results of the study show that the role of indigenous peoples in preventing and overcoming Covid-19 through local wisdom values in each sultanate is almost the same because what is meant by these local wisdom values has been inherited and preserved in their lives from generation to generation by adapting to the circumstances and conditions that occur. The synergy and pattern of handling carried out by the regional government and the sultanate in fighting Covid-19 in North Maluku is going well, this can be seen from the government's recommendations for the public to implement health protocols such as socializing the importance of wearing masks, washing hands and keeping their distance, and not there may be crowds at mosques, sultanates or palaces or places that are the gathering points of these indigenous peoples.